Clinicopathological Profile and Outcome of Acute Pancreatitis - Rahman, Md Anisur; Begum, Most. Umme Habiba; Sharmam, Praveen Kumar; Jha, Atul; Jain, Rahul; Singh, Sudhir Kumar (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Background: Acute pancreatitis is an important cause of morbidity and mortality among gastrointestinal disorders. But little is known about etiology and clinical profile in Indian population. Objective: To know clinicopathological profile, etiology and outcome of acute pancreatitis in study patients. Material and methods: This observational cross-sectional study was conducted in a tertiary care and research hospital in New Delhi India from May 2018 to November 2018. Total 30 established cases of acute pancreatitis were included in the study. Data were collected and processed by using SPSS version20 and result was obtained in tables and diagrams. Results: Among 30 patients, 21(70%) were male and 9(30%) female; 18 to 89 yrs of aged patients were included in the study with mean age 41.6±17.5 years, of 18-30 years of aged patients were more affected (10, 33.3%); patients of different occupation were studied;26(86.7%)patients were non-smoker and 4(13.3%) smoker; 16(53.3%) were non-alcoholic and 14(46.7%) patients had a habit of alcoholism of whom, all were male; patients who used to take e”5 units of alcohol per day were frequently affected (10, 71.4%) by acute pancreatitis, though it did not spared occasional drinkers (2, 14.3%);22(73.3%) patients had interstitial pancreatitis and 8(26.7%) had acute necrotizing pancreatitis;14(46.7%) patients had acute pancreatitis due to alcohol, 10 (33.3%) patients had gall stone, 2(6.7%) patients developed pancreatitis after ERCP;29(96.7%) patients presented with abdominal pain, 28 (93.3%) had vomiting, 21 (70%) patients had jaundice, 10 (33.3%) had fever, 18 (60%) patients had anemia, 17 (56.7%) patients develop ascites, 19 (63.3%) patients develop pleural effusion, 7(23.3%) patients developed ileus, and 3(10.0%) patients developed circulatory shock; 25(83.3%) patients developed organ dysfunction during in hospital care, of whom 11(36.7%) patients had transient and 14(46.7%) had persistent organ dysfunction; 5(16.7%) patients were complicated with pseudocyst, 6(20%) had walled of necrosis (WON), 7(23.3%) developed sepsis, 14(46.7%) developed renal dysfunction, 23(76.7%) developed hepatic dysfunction, 8(26.7%) developed respiratory dysfunction, 6(20%) developed pneumonia; 8(26.7%) patients had been suffering from different comorbidity; ultrasound of abdomen were abnormal in all 30(100%) patients; As per CTSI score, severe pancreatitis 14(46.7%), moderate pancreatitis 14(46.7%) and mild pancreatitis 2(6.7%); 24(80%) patients received only medical treatment and 6(20%) patients needed surgical or radiological intervention; 19(63.3%) patients were improved symptomatically, 8(26.7%) patients were cured and 3(10%) patients died during in hospital care. Conclusion: Alcohol was the predominant etiology of acute pancreatitis, mostly affecting young and middle aged male, but mortality was more in gall stone related pancreatitis. Hepatic dysfunction was observed frequently that may attribute to effect of chronic alcohol abuse. J Bangladesh Coll Phys Surg 2020; 38(2): 86-92